Innovations in Corneal Crosslinking. (1st February 2023) - Borgardts, Klara; Menzel-Severing, Johannes; Fischinger, Isaak; Geerling, Gerd; Seiler, Theo G.
Abstract: Purpose: Corneal Crosslinking (CXL) strengthens the keratoconus cornea and prevents further disease progression. Modified crosslinking protocols and different riboflavin solutions have been proposed to optimize the procedure and improve treatment success. Methods: PubMed research of relevant publications and report of own experiences with different CXL protocols. Results: Accelerated CXL shows comparable efficiency with shorter surgery time and similar complication rates. Customized CXL provides improved results with faster epithelial healing. CXL in a hyperoxic environment seems to be a safe and effective transepithelial alternative with presumably less complications and fewer side effects. Thin corneas (<400 µm) can be treated safely by corneal swelling using hypoosmolar riboflavin solutions and reducing the applied UV-energy. The combination of CXL with photorefractive keratectomy (PRK) can be considered in patients with contact lens intolerance improving visual acuity, however, with increased risk of visual loss compared to CXL alone. Two-Photon (2Ph) CXL is a promising new technology enabling three-dimensional CXL. Discussion: Recently developed CXL protocols offer advantages over the standard "Dresden-protocol" and should be considered in patients with progressive keratectasia.